Quantificational subordination as anaphora to a function - Gotham, M (Springer-Verlag Berlin Heidelberg, 2019)
In [11], a semantics for cross-sentential and donkey anaphora is presented that is inspired by approaches using dependent types but couched in simple type theory with parametric polymorphism. In this paper, the approach is extended to cover quantificational subordination. It is argued that the approach enjoys advantages over existing accounts in type-theoretical semantics.